A wideband millimetre-wave antenna array for 5G and next generation thin mobile terminals. Issue 3 (3rd July 2022) - Yu, Yifan; Wu, Yongle; Wang, Weimin; Yang, Yuhao
ABSTRACT: A millimetre-wave antenna array with a wide bandwidth and a high return loss for 5G and next generation thin mobile terminals is presented in this paper. The proposed antenna array is designed on the basis of the E-shaped patch antenna elements and an H-shaped feed network, and it uses the multilayer patch structure to achieve broad bandwidth. According to the simulated and measured results, the 15-dB bandwidth of the antenna array can cover 30.85–34.36 GHz. The proposed design is made of low-cost Rogers laminates with a simple structure so that it can be used in thin mobile terminals.